2000
DOI: 10.1103/physrevd.62.116009
|View full text |Cite
|
Sign up to set email alerts
|

Variational study of bound states in the Higgs model

Abstract: The possible existence of Higgs-Higgs bound states in the Higgs sector of the Standard Model is explored using the |hh + |hhh variational ansatz of Di Leo and Darewych. The resulting integral equations can be decoupled exactly, yielding a one-dimensional integral equation, solved numerically. We thereby avoid the extra approximations employed by Di Leo and Darewych, and we find a qualitatively different mass renormalization. Within the conventional scenario, where a not-too-large cutoff is invoked to avoid "tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
44
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 14 publications
6
44
0
Order By: Relevance
“…We have shown that a further increase of the coupling strength yields a decrease of the mass [12], and this has also been confirmed by recent Bethe-Salpeter calculations [13]. The physical reason is very simple: at tree level m is proportional to λ; however the interaction renormalizes the mass, since the attractive self-coupling reduces the energy of a free boson.…”
supporting
confidence: 66%
See 3 more Smart Citations
“…We have shown that a further increase of the coupling strength yields a decrease of the mass [12], and this has also been confirmed by recent Bethe-Salpeter calculations [13]. The physical reason is very simple: at tree level m is proportional to λ; however the interaction renormalizes the mass, since the attractive self-coupling reduces the energy of a free boson.…”
supporting
confidence: 66%
“…An exact decoupling can be easily achieved by the method of Ref. [12], thus avoiding any further approximation. The full details will be published elsewhere.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it would be also of interest to investigate the existence of bound states and related relativistic effects of the few-body Higgs bosons such as fourbody Higgs systems or even larger structures. For example, the existence of two-Higgs-boson bound states has been studied in references [33,34].…”
Section: Discussionmentioning
confidence: 99%